Analisis Kebutuhan Mode Deactivation Counseling untuk Mengendalikan Agresivitas Seksual Siswa Sekolah Menengah Pertama Inklusi - Barida, Muya; Widyastuti, Dian Ari (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study seeks to analyze the description of the need for Mode Deactivation Counseling (MDC) as an effort to control adolescent sexual aggressiveness. The research method used literature study and quantitative approach through a survey of 27 inclusive secondary school counselor across several regions in Indonesia. The MDC literature study rested on Mode Deactivation Therapy (MDT), while the survey results were analyzed through descriptive statistical analysis techniques by looking at the categorization of school counselors’ answers. The results show that school counselors need an effective way to control adolescent sexual aggressiveness and this can be done through the application of MDC.